Preconcentration strategies in the processing of nickel laterite ores Part 1: Literature review. (August 2015) - Quast, Keith; Connor, Jason N.; Skinner, William; Robinson, David J.; Addai-Mensah, Jonas
Highlights: Review of published literature on preconcentrating nickel laterites. Dominant industrial process is removal of coarse, gangue-rich material. Other physical separation techniques only applicable to small scale evaluation. Complex mineralogy compromises any significant nickel upgrading. Abstract: It is the aim of this paper to review previously reported studies and their relevance to the application of various techniques to physical methods of preconcentration of nickel (Ni) laterite ores prior to subsequent hydrometallurgical or pyrometallurgical processing. By far the most common preconcentration process used ahead of commercial hydrometallurgical processing of Ni laterites is the removal of a coarse fraction from the feed which has a lower Ni content than the finer material. This results in the production of a coarser reject product which is either stockpiled or processed by heap leaching. A number of other physical separation techniques for Ni laterites have been investigated at laboratory and pilot plant scale and reported in the open literature. These included sink-float (or dense media) separation, gravity separation, magnetic separation, electrostatic separation, (roasting) and flotation. The information located so far suggests that none of these techniques, although providing some degree of upgrading, have been incorporated into full plant operations suggesting that the potential upgrades achieved would not pay for their capital and operating costs. The general conclusion is that the complex mineralogy of Ni laterite samples compromises any significant upgrading in Ni values.